Introduction to embryonic and adult neural stem cells: from the metabolic circuits of the niches to the metabolome - Maria Antonietta Marcialis; Elisabetta Coni; Maria Cristina Pintus; Alberto Ravarino; Vassilios Fanos; Carlo Coni; Gavino Faa (Hygeia Press di Corridori Marinella, 2016)
Metabolomics has provided new insight into the biology that drives the phenotype of stem cells. During the recent years, metabolic circuits of embryonic and neural stem cells (NSCs) have been better elucidated. Many factors contribute to stem cell determination fate: metabolism, transcriptional signaling, epigenetics, extrinsic mechanisms such as short-range signals from the niche and humoral signals. The metabolism decides if a cell proliferates, differentiates or remains quiescent. Embryonic and adult NSCs share two features: they generate at least one daughter cell and can differentiate into specialized cells. NSCs use different pathways depending on their stage of differentiation: glycolysis is highest in proliferating stem cells and it is essential for stemness. Conversely, oxidative phosphorylation supports differentiated cells. Moreover, lipid metabolism maintains proliferation and neurogenesis; indeed, fatty acid oxidation and fatty acid synthesis represent a component of stem cell fate regulation. Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano